Methodological Approach to the Study of International Economic Integration Influence on Development of the EAEU Members - D.A. Shelestova; M.S. Tolstel; E.S. Starostina (Institute of Economic Research (IER), 2017)
Research background: In modern conditions the international integration processes act as pledge of a sustainable development of the states, activization of investment cooperation, implementation of joint perspective projects. The emergence of new international economic integration organizations predetermines the need to rethink the patterns of development models of international economic integration processes, especially in the context of their impact on the economies of the participating countries. The analysis methods for assessing the effects of the international economic integration (Bergeijk, Brakman (2010), Blomstrom, Kokko (1997), Kepaptsoglou, Karlaftis, Tsamboulas (2010), Michalopoulos, Tarr (1997), Plummer, Cheong, Hamanaka (2010), Zwinkels, Beugelsdijk (2010), Vinokurov (2010) shows that none of them alone doesn't allow a comprehensive assessment of the regional integration effects. Therefore, in the presence of statistical and other relevant information necessary to use the methods of quantitative analysis in the complex, taking into account their strengths and weaknesses, opportunities and constraints. Purpose of the article: The purpose of the study is to develop the theoretical foundations and development of methodology for assessing the impact of international economic integration in the socio-economic development of the participating countries (for example, the Eurasian Economic Union (EAEU)). Methodology/methods: The authors created methodological approach to the study of influence of international economic integration on development of the EAEU members based on reaching of target indexes of international movement of goods, services and factors of production. Findings & Value added: Depending on the value of the integral indicator, the authors list four levels of the economic potential of the countries participating in the EAEU. The presented methodological approach allows to early diagnose problem areas and to choose from a variety of management solutions for its improvement.
Keywords: C18; F02; F15; F36; F63; 330; international economic integration; Eurasian Economic Union (EAEU); economic development; globalization; economic potential